2020
DOI: 10.1039/d0ra01654c
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the promotion role of phosphorus doping on carbon as a metal-free catalyst for low-temperature selective catalytic reduction of NO with NH3

Abstract: P species can effectively enhance the catalytic activity of carbon aerogels for NO reduction at low temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…TPR profile of P‐CA also shows strong peaks at the temperature range of 400–600 °C. Our previous study indicated that C−O−P and C 3 −P=O groups are present on the surface of P‐CA, [22] and the reduction process of C−O‐P→C 3 ‐P=O→C 3 ‐P→elemental P can occur with the temperature rising in H 2 atmosphere, [40] resulting in a higher total H 2 consumption for P‐CA as shown in Figure 8b. In addition to the reduction of P‐containing functional groups at 300–700 °C, another possible reason for the shift of reduction peak to higher temperature of 10 %MnO x −CeO 2 /P‐CA compared with 10 %MnO x −CeO 2 /CA should be due to the intense interaction between MnO x and CeO 2 , mainly the reduction of the Mn‐O−Ce species occurs at this temperature range [39] …”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…TPR profile of P‐CA also shows strong peaks at the temperature range of 400–600 °C. Our previous study indicated that C−O−P and C 3 −P=O groups are present on the surface of P‐CA, [22] and the reduction process of C−O‐P→C 3 ‐P=O→C 3 ‐P→elemental P can occur with the temperature rising in H 2 atmosphere, [40] resulting in a higher total H 2 consumption for P‐CA as shown in Figure 8b. In addition to the reduction of P‐containing functional groups at 300–700 °C, another possible reason for the shift of reduction peak to higher temperature of 10 %MnO x −CeO 2 /P‐CA compared with 10 %MnO x −CeO 2 /CA should be due to the intense interaction between MnO x and CeO 2 , mainly the reduction of the Mn‐O−Ce species occurs at this temperature range [39] …”
Section: Resultsmentioning
confidence: 92%
“…The band at 1162 cm −1 and 1130 cm −1 is assigned to bulk‐like sulfate and bidentate sulfate, respectively [54] . The peaks at 1040 and 920 cm −1 are attributed to the stretching motion of surface coordination of bisulfite that is generated from the reaction of SO 2 and surface hydroxyl groups, [52] and our previous study has shown that much hydroxyl groups are present on the P‐CA surface [22] . Figure 12b shows the in‐situ DRIFT spectra of SO 2 +O 2 adsorption on the 10 %MnO x −CeO 2 /CA catalyst [52] .…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Therefore, Pt/CNF-HT and Pt/N-CNF are less acidic catalysts compared to the other catalysts. Pt/P-CNF exhibited the highest desorption peak at 210 °C, most likely associated with P–OH, which is favorable for coordinating with NH 3 . Next in acidity, Pt/B-CNF has the highest desorption peak at 180 °C, including a shoulder at 255 °C, which may be related to oxidized boron species, as revealed by XPS analysis (Table S4).…”
Section: Resultsmentioning
confidence: 99%